2023
DOI: 10.13057/biodiv/d240522
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the effect of ENSO and IOD on the productivity of yellowfin tuna (Thunnus albacares) in the South Indian Ocean, East Java, Indonesia

ABU BAKAR SAMBAH,
AURUM NOOR’IZZAH,
CANDRA ADI INTYAS
et al.

Abstract: Abstract. Sambah AB, Noor’izzah A, Intyas CA, Widhiyanuriyawan D, Affandy DP, Wijaya A. 2023. Analysis of the effect of ENSO and IOD on the productivity of yellowfin tuna (Thunnus albacares) in the South Indian Ocean, East Java, Indonesia. Biodiversitas 24: 2689-2700. Yellowfin tuna (Thunnus albacares) is one of the fish that migrates through the Indian Ocean and is primarily caught in the south Java waters which are directly adjacent to the Indian Ocean. Fish abundance and migration are influenced by oceanogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
(51 reference statements)
0
2
0
Order By: Relevance
“…This condition was supported by previous studies that found that the Southeast monsoon period from June to August associated with El-Niño and positive IOD events in the southern waters of Indonesia triggered the upwelling causing the nutrients, including the concentration of chlorophyll-a, to increase. The ENSO and IOD phenomena that occur in the EIO influence the existence of tuna through the dynamics of changes in the distribution of oceanographic parameters (Sambah et al 2023). The current trend figure describes the confluence of several currents flowing into this region such as ITF.…”
Section: Relationship Between Fronts and Eddies Event With The Format...mentioning
confidence: 99%
“…This condition was supported by previous studies that found that the Southeast monsoon period from June to August associated with El-Niño and positive IOD events in the southern waters of Indonesia triggered the upwelling causing the nutrients, including the concentration of chlorophyll-a, to increase. The ENSO and IOD phenomena that occur in the EIO influence the existence of tuna through the dynamics of changes in the distribution of oceanographic parameters (Sambah et al 2023). The current trend figure describes the confluence of several currents flowing into this region such as ITF.…”
Section: Relationship Between Fronts and Eddies Event With The Format...mentioning
confidence: 99%
“…Environmental variation impacts on tuna resources can studied and quantified using models that incorporate environmental variables (Sambah et al, 2023;Taboada et al, 2023;Wang et al, 2023). These models normally require environmental data over decadal timescales, which are not always readily available and may not be always of reliable quality.…”
Section: Introductionmentioning
confidence: 99%